INFLUENCE OF LANGUAGE LEARNING STRATEGIES ON SELF-EFFICACY AMONG MALAYSIAN MASS COMM UNDERGRADUATES - Mokhtar, Muhammad Irfan; Anuar, Nur Alyani (PEOPLE: International Journal of Social Sciences, 2015)
According to Gahungu (2007), learners’ use of learning strategies can influence their language learning ability and affect their self-efficacy. There are 6 strategies namely memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies and social strategies. Self-efficacy is a skill that is not already embedded in the self of a learner. It is generated and developed. Past researches have shown the relationship between language learning strategies and learners’ self-efficacy. This study aims to look into detail on students’ preferences of strategies and how those strategies affect their level of proficiency in second language acquisition. The result of this study will show interesting findings on how language learning strategies influence self-efficacy.